Evaluation of the microbial viability of soil samples from maize crops in freeze-storage under different management conditions in a semi-arid climate - Ramirez, Manuel (2017)
The effect of freeze-storage on culturable soil microorganism viability was determined for soil samples from three agricultural maize crop systems (under conventional management, direct seeding, and direct seeding with a cover crop). Most culturable soil bacteria were unaffected by the freeze-thaw stress or the prolonged freeze-storage, but the viability of mold and Bacillus mycoides populations decreased drastically after eight months of freeze-storage, limiting the process sustainability to this period. However, these changes did not significantly affect either the total microorganism biodiversity index or the biodiversity differences between treatment. Based on the available results, freeze-storage seems to be a sustainable process for up to eight months that can be allowed in analyses of culturable microbial population biodiversity